Orthodontic Treatment of Anterior Open Bite Caused by a Car Accident - Naoto Hirose; Makoto Yanoshita; Sayuri Nishiyama; Naoki Kubo; Daiki Kita; Eri Tsuboi; Kotaro Tanimoto (Contemporary Clinical Dentistry)
This article outlines the orthodontic treatment of a 21-year-old female patient with an open bite and temporomandibular joint disorders (TMDs) that developed after a severe car accident. The treatment plan utilized temporary anchorage devices (TADs) for upper molar intrusion to correct the open bite without resorting to orthognathic surgery. Over a period of 3 years, the treatment achieved a stable occlusion, normalized molar relationships, and improved esthetics. Despite the persistent of TMD symptoms, the patient experienced enhanced jaw movement and a reduction in abnormal chewing cycles. The combination of orthodontic treatment with TADs and splint therapy contributed to successfully restoring both esthetic and functional aspects. This case underscores the efficacy of TADs in addressing trauma-induced malocclusions, highlighting the potential for minimal intervention to achieve comprehensive treatment outcomes.